The Minibus Taxi Industry’s Communication Strategies in Dealing with Linguistic Diversity on the Way to Business Leadership: The Case of South Africa - Phumzile Masala (Business Ethics and Leadership, 2023)
Informal businesses, such as the minibus taxi industry, positively contribute to the country’s economy whilst providing an essential public transport service to the linguistically diverse communities of multilingual South Africa. The systematisation of the scientific literature on the development of the minibus taxi industry proved the absence of comprehensive studies aimed at understanding the communication strategies that taxi operators use among themselves and when interacting with passengers. This paper aims to investigate the types of language strategies that take place in six taxi associations in which IsiZulu and English are the two dominant languages. This investigation is conducted against the multilingual context of the country and its attractiveness as an international and domestic tourist destination to determine how the business leadership in the taxi industry responds. The article’s theoretical framework draws from the transformative paradigm as it enables one to explore the experiences of marginalised communities. In this case, the marginalised communities are the taxi operators who stand to benefit from appropriate communication strategies. By taking the initiative and showing “agency”, they direct their efforts to solve existing problems in communication with passengers. The qualitative approach was adopted as a research methodology in which the researcher selected a structured interview approach. It involved interviews with twenty-four taxi operators and drivers who were purposefully selected in eThekwini Metropolitan Municipality in the KwaZulu-Natal province of South Africa. The participants gave an account of their experiences of bi-/multilingualism in the taxi industry during taxi association meetings, when interacting informally among themselves and in their communication with passengers. The results of the analysis of the responses of the respondents showed that the communication strategies used to mediate challenges posed by linguistic diversity are translation, interpretation, slang and language dominance. It is concluded that through their agency and by taking initiatives to deal with linguistic challenges in the eThekwini taxi industry, the economically marginalised are to be commended for being able to resolve impediments to their economic growth.